Effects of Drink Driving on Crash Risk Based on Random Breath Test Data. Issue 3 (May 2013) - Li, YC; Sze, NN; Wong, SC; Tsui, KL; So, FL
Introduction: Driving under the influence of alcohol (DUIA) is an important contributor to road crashes, injuries, and fatalities. Legal limits on drivers' breath alcohol concentration (BrAC) were first introduced in Hong Kong during the 1990s. Since then, the number of alcohol-related crashes has decreased. In 2009, police were empowered to conduct random breath tests (RBT) at roadblocks at any time. The availability of comprehensive RBT data allows us to determine the relationship between crash risk and BrAC, while controlling for confounding factors such as temporal distribution, road environment, and traffic conditions. Method: In this study, we established two negative binomial regression models to analyse the risk of crashes in which people are killed or seriously injured (KSI crashes) and those involving only slight injuries on 182 urban road segments. Results: Our results indicated that a higher mean BrAC markedly increases the risk of KSI crashes. However, there was no relationship between the risk of crashes involving slight injury and mean BrAC, although the absence of a hard shoulder, the presence of roadside parking bays, the dawn period, and the location noticeably increase the risk of these crashes. Conclusion: It is worth exploring the benefits of remedial measures if comprehensive information on demographics and the driving habits of individual drivers become available in the future.